Cultural differences in social comparison on Facebook. Issue 2 (1st February 2019) - Song, Hayeon; Cramer, Emily M.; Park, Namkee
ABSTRACT: Delving into motivations for and the impact of social comparison among students in the U.S. and South Korea, the present study examined cross-cultural differences in social comparison on Facebook. Following Helgeson and Mickelson [1995. "Motives for social comparison." Personality and Social Psychology Bulletin 21 (11): 1200–1209. doi:10.1177/01461672952111008 .]'s framework, social comparison was studied both offline and online based on a range of motivations rather than targets of social comparison. Results suggested an insignificant effect of culture on orientation toward social comparison. However, significant cultural differences were observed in motivations for social comparison. The U.S. participants, compared to their South Korean counterparts, demonstrated a greater propensity both offline and online to engage in social comparison motivations of self-enhancement and altruism. On Facebook, South Korean participants' social comparison motivations for self-improvement, common bond, and self-destruction were higher than those of the U.S. participants. The U.S. participants generally felt more positive and less fatigued after making comparisons on Facebook. Factors influencing post-comparison affect were also investigated between the two countries.